Analisis disparitas pembangunan antar Kabupaten/Kotadi Provinsi Jambi (segi ekonomi dan non ekonomi) - Safitri, Erni; Junaidi, Junaidi; Erfit, Erfit (Jurnal Paradigma Ekonomika, 2021)
This study aims to: (1) analyze the level of development inequality in districts/cities in Jambi Province. (2) analyze the factors that influence the level of development inequality from an economic and non-economic perspective between regencies/cities in Jambi Province. (3) Analyze the government's policies to overcome the inequality problem in Jambi Province. Based on the research results, (1) The average level of development inequality between districts/cities in Jambi Province is 0.18, lower than the rate of inequality in Indonesia. The province that is almost close to a high level of inequality is Kota Sungai Penuh, which is 0.49 points. At the same time, the smallest is Sarolangun Regency, which is 0.01. (2) From an economic perspective, the variables that significantly affect development inequality are balancing funds and investment, while the variable economic growth has no significant effect. From a non-economic perspective, only the human development index significantly affects development inequality, while labor and poverty have no significant effect. Â